Motivasi Kerja sebagai Variabel Intervening antara Budaya Organisasi dan Gaya Kepemimpinan Terhadap Kepuasan Kerja - Grace Fredriksz; Shirley Fredriksz (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
Agriculture is the field closest to people's lives, especially in rural areas. The government must continue to provide advice and in this case the Western Moluccas Department of Agriculture is responsible for contributing to these activities. Therefore, it is necessary to prepare quality human resources. The purpose of this study is to determine the influence of organizational culture and leadership style on job satisfaction through motivation in the SBB District Department of Agriculture. The sampling technique used in this study is purposive sampling technique and the research sample includes 42 employees. The data obtained through the distribution of questionnaires were then analyzed using inferential statistical analysis techniques, specifically Partial Least Squares (PLS) with Smart-PLS 3 software. This study shows that organizational culture and leadership style do not directly affect job satisfaction. However, organizational culture and leadership style have an indirect impact on job satisfaction through work motivation.